Electrical Industry Restructuring: From Policy to Implementation - Richert, Evan (Maine Policy Review, 1996)
Both in Maine and nationally, there is continuous evidence of fundamental transformation of the electric utility industry. Maine Policy Review continues coverage of this issue with Evan Richert’s summary of the June 1996, fifth annual conference on Public Utility Regulation and the Environment (PURE). Richert relates the conference discussions to the PUC’s July 1996 draft plan on electric utility industry restructuring and to state government’s efforts to create a comprehensive energy policy for Maine.